An experimental study on kind and generic readings across languages: bare plural vs. definite plural - Driemel, Imke; Hein, Johannes; Carioti, Desiré; Wünsch, Jakub; Tsakali, Vina; Alexiadou, Artemis; Sauerland, Uli; Guasti, Maria Teresa (Proceedings of the Amsterdam Colloquium, 2025)
To express kind and generic readings, Romance languages like Italian have been reported to use definite plurals but Germanic languages like English make use of bare plurals (Krifka et al., 1995; Chierchia, 1998), where Greek patterns with Romance (Alexiadou et al., 2007). German is discussed as an exception, as both bare and definite plurals are used to express kind (Krifka et al., 1995) and generic (Longobardi, 1994) readings. We present results from an experimental study comparing English, German, Italian and Greek, focusing on two novel findings: i) German and English both express kind/generic readings with bare plurals; ii) the effect of speaker distance (Acton, 2019) makes the definite plural an additional option in German.